2011
DOI: 10.1128/jb.01353-10
|View full text |Cite
|
Sign up to set email alerts
|

A Glutathione Redox Effect on Photosynthetic Membrane Expression in Rhodospirillum rubrum

Abstract: The formation of intracytoplasmic photosynthetic membranes by facultative anoxygenic photosynthetic bacteria has become a prime example for exploring redox control of gene expression in response to oxygen and light. Although a number of redox-responsive sensor proteins and transcription factors have been characterized in several species during the last several years in some detail, the overall understanding of the metabolic events that determine the cellular redox environment and initiate redox signaling is st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…The prevalent hypothesis is that both the high level of bicarbonate ions and the genomic amplification in the acetate-competent strain help in dealing with the redox imbalance produced by the culture dilution at inoculation or a sudden light intensity increase. Our experiments demonstrated that high light intensity impacted photosynthesis and pigment metabolisms, confirming the findings of other groups (Carius et al, 2011;Niederman, 2013). Furthermore, the light stress also influenced the central carbon metabolism of Rs.…”
Section: Resultssupporting
confidence: 90%
“…The prevalent hypothesis is that both the high level of bicarbonate ions and the genomic amplification in the acetate-competent strain help in dealing with the redox imbalance produced by the culture dilution at inoculation or a sudden light intensity increase. Our experiments demonstrated that high light intensity impacted photosynthesis and pigment metabolisms, confirming the findings of other groups (Carius et al, 2011;Niederman, 2013). Furthermore, the light stress also influenced the central carbon metabolism of Rs.…”
Section: Resultssupporting
confidence: 90%
“…As reported previously, PrxQ deficiency can up-regulate the levels of mRNAs encoding glutathione reductase and glutathione synthetase [ 35 ], thus decreasing GSTF3 and GSH contents, and the GST activities observed in this research might be regulated by PrxQ. Furthermore, alterations to GST and GSH levels might affect PSI via their functions in hydrogen peroxide degradation and photosystem protection [ 6 , 36 ].…”
Section: Discussionsupporting
confidence: 73%
“…A lack of reducing equivalents caused by a decreasing fructose uptake could offer a simple explanation for this observation. It has been suggested by Carius and Grammel (Carius et al, 2011) that reducing equivalents, provided by the degradation of fructose, might induce the PM production by lowering the total cellular redox potential. However, the fructose uptake rates calculated in this study remain constant at a value of 0.75 ± 0.04 mmol(g h) −1 over a ΔCRP range from −160 to −330 mV.…”
Section: Resultsmentioning
confidence: 99%